Strategi Bersaing Agency Mthree Communication Dalam Industri Periklanan Nasional - Linda Wardhani; Eko Harry Susanto (Universitas Tarumanagara, 2020)
Competition in the national advertising service industry is currently getting tougher, but the development potential of the advertising service industry is still quite good, especially in big cities that follow very rapid development. Advertising basically will never be lonely as seen from its function in introducing products that have effective and efficient usability properties, this of course makes more and more competitors also make the greater competition that will occur, if this is needed a business strategy that is able to compete. This research aims to determine whether the most appropriate strategy is used for Mthree Communication Advertising in the face of competition in the national advertising industry. This research was conducted in the Mthree Communication Advertising environment, with resource persons of employees who have strategic positions in the company's business and have a service life of more than 5 years. Research conducted using qualitative methods by conducting a SWOT analysis to identify strengths (weaknesses), weaknesses (weaknesses), opportunities (opportunities), and threats (threats). From the SWOT analysis, a SWOT matrix will be created which is useful for formulating alternative strategies for the company. From the results of the research that has been carried out, it has been concluded that the right competitive strategy for the company is the focus strategy, which is to provide maximum services to clients who are running until now.